The outdoor recreation potential of the Garden Route area: a study of the demand for outdoor recreation in a mobile population and evaluation of the Garden Route Area as a supplier of this demand - Barry, Reginald Louis (School of Architecture, Planning and Geomatics, 2020)
Recent newspaper headlines announced "Coastal plot prices up 500 per cent - SOUTHERN CAPE LAND SCRAMBLE" and reference was made to the big demand for plots at coastal resorts between Mossel Bay and Knynsa, and the holiday trade's interest in such big hotel deals as R400,000 at The Wilderness. ''Local authorities and businessmen feel the upsurge in demand for property, may indicate that the Southern Cape is set to take over "holiday mecca of the country". While the echo of these super cents in the till is deadening even the sound of the sea to some, other's concern is sending a chill down the spine. Many, during their active lives, craved for a slaver pace of living. Many found it here, and called it Hunter's Home, and Leisure Isle. Nov they see man's restlessness give a new scale to his pursuit of leisure.